2016
DOI: 10.11648/j.ajpn.20160402.12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nootropic Activity of <i>Persicaria flaccida</i> on Cognitive Performance, Brain Antioxidant Markers and Acetylcholinesterase Activity in Rats: Implication for the Management of Alzheimer’s Disease

Abstract: Oxidative stress is the leading cause of neurodegenerative diseases, especially Alzheimer´s disease (AD). The plant Persicaria flaccida (PF) is known in Bengali as red Biskatali belongs to family Polygonaceae. Preliminary studies have shown the antioxidant, anti-inflammatory, analgesic, neuroprotective activities of Biskatali. In this consequence, methanolic extract of PF (MEPF) was selected to explore the ability of this plant to enhance cognitive functions, brain antioxidant enzymes and anti-acetylcholineste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The current study showed that administration of EEPR pointedly increases the level of brain antioxidant enzymes and decrease the levels of TBARS. In the study of nootropic activity of aerial parts of Persicaria flaccida on brain antioxidant markers and cognitive performance of rats by Uddin et al, also reported equivalent results [84].…”
Section: Discussionmentioning
confidence: 92%
“…The current study showed that administration of EEPR pointedly increases the level of brain antioxidant enzymes and decrease the levels of TBARS. In the study of nootropic activity of aerial parts of Persicaria flaccida on brain antioxidant markers and cognitive performance of rats by Uddin et al, also reported equivalent results [84].…”
Section: Discussionmentioning
confidence: 92%
“…A plausible reason behind such a superior antibacterial activity for rGO-AuNPs synthesized from P. salicifolia is that the extract of P. salicifolia contains several antioxidant, analgesic, antimicrobial, and antitumor active biochemical ingredients. 86 , 87 Furthermore, these plants were proven to have many medicinal benefits 50 as they contain phenolic acids, glycosides, terpenoids, and flavonoids. In addition, a comparison between the antibacterial activity of AuNPs, rGO-AuNPs, and other nanomaterials is given in Table 2 to indicate the high antibacterial efficiency of rGO-AuNPs, which is better than various previously reported results.…”
Section: Resultsmentioning
confidence: 99%
“…The human brain is the centre for controlling physical as well as emotional activities. It is responsible for 'cognition' which is one of the salient characteristics of human beings [2]. The hippocampal, cortical and cerebellar areas of the brain are responsible for the memory processes.…”
Section: Introductionmentioning
confidence: 99%